Potentials and challenges in early involvement of citizens in coproduction in the form of co-governance - Agger, Annika (Politica, 2015)
Few studies of co-production in the form of co-governance focus on early involvement of citizens in the input stage of a policy process. What kinds of challenges and potentials does this form of co-production bring about when citizens, local councilors and public administrators collaborate to develop public policies? The empirical foundation for the article is a study of a Danish municipality, Albertslund, where six local councilors, six citizens and three public administrators participated in a formal committee with the purpose of developing a new municipal policy for citizen participation. The study concludes that citizens improve their democratic capabilities and trust in the political establishment in the municipality by participating in the committee. However, a condition for realizing the potentials is a willingness to collaborate in new and more interactive ways.